Knowing the Role of the Teams Games Tournament Cooperative Learning Model on Student Learning Activeness - Ghaemi, Mohammad; Ebrahimi, Esmail; Ocak, Pariyaporn (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
Background: This study aimed to investigate the impact of the Teams Games Tournament (TGT) cooperative learning model on student learning engagement in the subject of Ecosystem. Method: The research was conducted at a Middle School in Muscat, Oman, utilizing cluster random sampling. The study involved two groups: a control group and an experimental group. The research design employed was a quasi-experiment with a posttest-only control design. Data analysis was conducted using the t-test with a significance level of 1%. Data collection techniques included observation and questionnaires. Results: The hypothesis test results revealed a t-test value of 8.1, whereas the critical t-table value was 2.66. The calculations indicated that t-test > t-table, leading to the rejection of H0. This finding indicates that students responded positively to the learning experience using the (TGT)cooperative learning model. Conclusion: In conclusion, implementing the (TGT)cooperative learning model enhanced student learning activity in Ecosystem education.